Instrumen Tes Berpikir Kritis Pada Materi Hukum Coulomb - Ramadhani, Anggi Adelia; Suhadi; Mabruroh, Faizatul; Putri, Jami’atul Khairunnisa; Sairi, Andi Putra; Widya, Herma (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2026)
This study aims to develop a critical thinking skills test instrument on the Coulomb's Law material that meets the qualifications including aspects of feasibility validation, validity and reliability. This study is a development research with the ADDIE approach. This study was conducted at SMA Negeri 1 Payaraman with a sample of 30 students in class XII.3. The results showed that the test instrument was declared feasible based on the feasibility validation test, valid based on the validity test and reliable based on the reliability test. The average feasibility validation score was 3.66, with a feasible category. The validity test stated that the r count of all test instruments > r table (0.361) and the reliability value was 0.733.